EKOENZIM SEBAGAI PENGENDALIAN PATOGEN Fusarium sp. DAN Colletotrichum sp. PADA TANAMAN PISANG BARANGAN (Musa acuminata) - Burdah Asni; Syafrina Sari Lubis; Diannita Harahap (KENANGA : Journal of Biological Sciences and Applied Biology, 2023)
Barangan banana (Musa acuminata) belongs to Musaceae family which has hig economic value and has the potential as a commercial material and food diversification. One of the diseases of Barangan banana (Musa acuminata) which causes quite high damage is Fusarium sp. wilt disease. and anthracnose disease Colletotrichum sp. This study aims to control Fusarium sp. and Colletotrichum sp. using ecoenzymes in this study ecoenzymes were made from fruit peel waste which was fermented for three months. Testing the activity of controlling Fusarium sp. and Colletotrichum sp. using the diffusion method. Ecoenzymes phytochemical test results contained alkaloids and saponins. Ecoenzymes at concentrations of 10% - 40% showed strong and very strong activity against Fusarium sp. while Colletotrichum sp. 20% concentration shows very strong activity.